Carbon fiber intramedullary nail and preparation method thereof

By adopting the preparation method of carbon fiber intramedullary nails, mixed fiber composite rope strands and spiral designs, the integrated molded carbon fiber intramedullary nails are solved, and the existing intramedullary nails are gradually degraded and bone integration are achieved.

CN119680024APending Publication Date: 2025-03-25SHANDONG WEIGAO ORTHOPEDIC DEVICE COMPANY

Patent Information

Application Number
CN202411615013.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing orthopedic implants such as intramedullary nails have poor integration effect in the body, degradation speed is too fast, unable to match the speed of bone growth and recovery, and the material is insufficient inert bioinflammation, which cannot promote bone integration.

Method used

The method of preparing carbon fiber intramedullary nails is adopted to prepare mixed fiber composite rope strands by spiral wound the outer layer of fibers and axially loaded and twisted, hot pressed, cooling and heat treatment, forming a spiral carbon fiber prefabricated body, and pre-embedded molds form screw holes, and finally obtain integrated carbon fiber intramedullary nails. The intramedullary nail contains polyaryletherketone resin fibers, carbon fibers and biodegradable metal fibers to ensure gradual degradation and bone integration in the body.

Benefits of technology

It achieves gradual degradation in the body while maintaining sufficient mechanical support, matching the bone healing cycle, promoting precise healing, and overcoming the problems of poor integration effect of traditional intramedullary nails in the body and excessive degradation speed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680024A_ABST
    Figure CN119680024A_ABST
Patent Text Reader

Abstract

The invention provides a carbon fiber intramedullary nail and a preparation method thereof, and relates to the technical field of orthopedic implants, at least two layers of outer layer fibers are spirally wound around a central fiber to prepare a hybrid fiber composite rope strand; the hybrid fiber composite rope strands are axially loaded and twisted with the core mold as the center, a spiral carbon fiber prefabricated body is formed, and a mold is pre-buried in the carbon fiber prefabricated body to form screw holes; the carbon fiber prefabricated body is sequentially subjected to hot pressing, cooling and heat treatment, the carbon fiber intramedullary nail is obtained, and fibers of the hybrid fiber composite rope strand comprise polyaryletherketone resin fibers, carbon fibers and biodegradable metal fibers. The biodegradable metal fiber is used as a pore-forming fiber, a series of porous intramedullary nails with accurate pore size distribution can be obtained, and the porous intramedullary nails have the characteristics of cancellous bone-like hierarchical pore sizes while having high connectivity; by means of gradual degradation of the metal fibers in the body, the nail body is gradually transited from firm fixation to biological fixation, the human skeleton healing cycle is matched, and the purpose of precise healing is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of orthopedic implants, and more specifically, to a carbon fiber intramedullary nail and a preparation method thereof. Background Art

[0002] Intramedullary nail is an internal fixation device inserted into the medullary cavity at the distal and proximal ends of the fracture. In Europe and the United States, its application rate for the treatment of long tubular bone fractures has reached more than 90%. Common intramedullary nail materials include metal materials such as titanium alloy, stainless steel and cobalt-chromium alloy. During in vivo service, there are problems such as poor implant integration, low patient comfort due to excessive weight, and interference artifacts in imaging examinations. In order to improve the bone integration effect of implant materials, the technical solutions used in the prior art are:

[0003] (1) Chinese invention patent with publication number CN105818492A, a bioactive phosphate-based continuous glass fiber textile composite material and its use, discloses a bioactive phosphate-based continuous glass fiber textile composite material comprising a bioactive phosphate-based continuous glass fiber fabric and a biocompatible polymer, or comprising a blended fabric and a biocompatible polymer, wherein the blended fabric is a blended fabric of bioactive phosphate-based continuous glass fiber and polylactic acid fiber. The mechanical properties of the bioactive phosphate-based continuous glass fiber textile composite material provided by the scheme reach the level of human bones, and the strength retention rate is above 50% after being immersed in phosphate buffer (PBS) for 7 weeks.

[0004] (2) Chinese invention patent with publication number CN112451752A, a high-strength degradable intramedullary nail and a manufacturing method thereof, the intramedullary nail is composed of three parts: an outer layer, a middle layer and an inner layer, the outer layer is a porous structure with a porosity of 40-90% and a pore size of 100-600 microns, the middle layer is a solid structure, the inner layer is a porous structure with a porosity of 60-90% and a pore size of 200-1000 microns, the entire intramedullary nail is made of bioactive materials and has a uniform cross section. The intramedullary nail of the present invention has high mechanical strength and is degradable in the body, does not require secondary surgery to remove, and has good biological activity and can promote fracture healing.

[0005] However, although the above materials meet the initial implant strength requirements, they degrade in an overall manner. As they degrade in the body, they lose their overall mechanical support, and the degradation rate is too fast to match the bone growth recovery rate.

[0006] (3) Chinese utility model patent with publication number CN221205624U, a continuous carbon fiber reinforced polyetheretherketone composite bone fixation plate, discloses a continuous carbon fiber reinforced polyetheretherketone composite bone fixation plate in which continuous carbon fiber reinforced polyetheretherketone composite wire is laid on a plane according to a wire laying path and stacked in the thickness direction to a target thickness; a plurality of wire laying paths are provided, and the plurality of wire laying paths are arranged in parallel; the wire laying paths are closed and surrounded along the screw hole. However, although this solution ensures the long-term strength of the implant, polyetheretherketone and carbon fiber are both bio-inert materials and cannot meet the requirements of bone tissue ingrowth and bone integration.

[0007] Therefore, there is a need for a composite bone implant product that can gradually achieve bone integration as the implant material naturally degrades in the body, while maintaining sufficient supporting strength during its degradation process. Summary of the invention

[0008] In order to solve the above problems, the technical solution adopted in this application is a method for preparing a carbon fiber intramedullary nail, comprising the following steps:

[0009] At least two layers of outer fibers are spirally wound around a central fiber to prepare a hybrid fiber composite rope strand; the hybrid fiber composite rope strand is axially loaded and twisted around a core mold to form a spiral carbon fiber preform, and a mold is embedded in the carbon fiber preform to form a screw hole; the carbon fiber preform is hot-pressed, cooled and heat-treated in sequence to obtain an integrally formed carbon fiber intramedullary nail, wherein the fibers of the hybrid fiber composite rope strand include polyaryletherketone resin fibers, carbon fibers and biodegradable metal fibers.

[0010] Optionally, the central fiber of the mixed fiber composite rope strand is the first layer of fiber, the polyaryletherketone resin fiber is arranged in the third layer or the outer layer, the first layer of fiber and the second layer of fiber are carbon fiber and / or biodegradable metal fiber, and the third layer and the outer layer of fiber are one of carbon fiber, biodegradable metal fiber and polyaryletherketone resin fiber or any combination thereof.

[0011] Optionally, the biodegradable metal fiber includes a combination of one or more of pure zinc fiber, pure magnesium fiber, pure iron fiber, magnesium-based alloy fiber, zinc-based alloy fiber and iron-based alloy fiber.

[0012] Optionally, the fineness of the polyaryletherketone resin fiber is 90-550 tex, the fineness of the carbon fiber is 35-330 tex, and the fineness of the biodegradable metal fiber is 35-280 tex.

[0013] Optionally, the twisting distance of the polyaryletherketone resin fiber, the carbon fiber and the biodegradable metal fiber wrapped around the central fiber is 50-200 mm.

[0014] Optionally, the hybrid fiber composite rope strands are wound onto a supporting mandrel at a constant angular rate, wherein the constant angular rate is 3° / min-10° / min.

[0015] Optionally, the length of the carbon fiber preform is 170-420 mm, the axial compression load of the axial loading twisting is 5-10 N, the diameter of the screw hole is 2-8 mm, and the cross-section of the metal fiber is circular, elliptical, flat, trapezoidal or wedge-shaped.

[0016] Optionally, hot pressing includes sealing the carbon fiber preform with a vacuum bag and sequentially undergoing a preheating process and a pressurizing process in an autoclave, and the pressurizing process sequentially includes three stages: constant pressure heating, constant pressure insulation and constant pressure cooling; cooling includes demoulding after naturally cooling to room temperature after the pressurizing process; heat treatment includes placing the demoulded carbon fiber preform in a heated heat treatment equipment for insulation, and then undergoing a cooling process and a natural cooling process.

[0017] Optionally, the pressurizing medium of the pressurization process is compressed air or nitrogen, the pressure increase / depressurization rate of the constant pressure heating and constant pressure insulation process is 0-0.1MPa / min, the constant pressure is 0.1-0.6MPa, the heating rate of the constant pressure heating stage is 3-8℃ / min, the constant pressure is heated to 360-420℃, the constant pressure insulation time is 0.2-1h, the cooling rate of the constant pressure cooling stage is 0.5-3℃ / min, and the temperature after cooling is 130-150℃; the heat treatment temperature is 170-250℃, and the heat treatment time is 2-12h; the cooling rate of the cooling process is 0.2-2℃ / min, and the temperature after the cooling process is 120-160℃.

[0018] The present application also provides a carbon fiber intramedullary nail, which is prepared by any one of the above-mentioned carbon fiber intramedullary nail preparation methods.

[0019] The beneficial effects of the present invention are:

[0020] According to the mechanical design requirements of carbon fiber composite intramedullary nails, the type combination, arrangement distribution and twisting method of the mixed fiber yarns used are flexibly matched to overcome the poor interlayer bonding of traditional composite products and improve the overall structural strength; the spiral hollow structure design makes the reinforcement yarns continuous and parallel, which is conducive to uniform load bearing when the material is stressed. The spiral reinforcement fiber layer can resist crack propagation during impact fracture and increase the overall safety and stability of the intramedullary nail structure; biodegradable metal fibers are used as pore-forming fibers to obtain a series of porous intramedullary nails with precise pore size distribution, which have high connectivity and the characteristics of multi-level pore sizes similar to cancellous bone; the gradual degradation of metal fibers in the body is utilized to gradually transition the nail body from solid fixation to biological fixation, matching the human bone healing cycle and achieving the purpose of precise healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art.

[0022] Figure 1 A schematic diagram of the overall structure of a carbon fiber intramedullary nail provided in an embodiment of the present application;

[0023] Figure 2 A cross-sectional view of a hybrid fiber composite rope strand provided in an embodiment of the present application;

[0024] Figure 3 This is a cross-sectional view of a carbon fiber intramedullary nail provided in an embodiment of the present application.

[0025] Explanation of the accompanying drawings: 1-polyetheretherketone fiber; 2-magnesium zinc alloy fiber; 3-carbon fiber. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0027] Example 1

[0028] like Figure 2 As shown, the outer layer fibers are spirally wound around the central fibers to prepare a hybrid fiber composite strand. In this embodiment, the central fiber (first layer fiber) is a carbon fiber 3 with a single fiber fineness of 200 tex and a twist pitch of 75 mm. The second layer fiber is a magnesium zinc alloy fiber 2 with a single fiber fineness of 100 tex, a twist pitch of 75 mm, and a circular cross section. The third layer fiber is a polyetheretherketone fiber 1 with a fineness of 200 tex and a twist pitch of 75 mm. The second layer fiber and the third layer fiber are twisted in parallel in the Z direction relative to the central fiber to obtain a carbon fiber / magnesium zinc alloy / polyetheretherketone hybrid fiber composite strand.

[0029] like Figure 3 As shown, the hybrid fiber composite rope strand is axially loaded and twisted around the core mold to form a Figure 1 The spiral carbon fiber preform shown in the figure is provided, and a screw hole is formed by pre-embedded mold in the carbon fiber preform; the hybrid fiber composite rope strand is wound onto the supporting core mold at a constant angular velocity, and the hybrid fiber composite rope strand is wound onto the supporting core mold at a constant angular velocity of 3° / min in the Z direction in a cylindrical spiral state, so as to obtain a straight-wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 170 mm). During the process, an axial compression load of 5N is applied to the core mold, and the core mold and the torsion device are kept coaxial. At the same time, screw holes are formed in the preform by pre-embedded mold, and the screw holes are symmetrically arranged with a hole diameter of 2.0 mm.

[0030] The carbon fiber preform is sequentially hot pressed, cooled and heat treated to obtain an integrally formed carbon fiber intramedullary nail.

[0031] Hot pressing includes sealing the carbon fiber preform with a vacuum bag and sequentially undergoing a preheating process and a pressurizing process in an autoclave, and the pressurizing process sequentially includes three stages: constant pressure heating, constant pressure insulation and constant pressure cooling; cooling includes demoulding after natural cooling to room temperature after the pressurizing process; heat treatment includes placing the demoulded carbon fiber preform in a heated heat treatment equipment for insulation, and then going through a cooling process and a natural cooling process.

[0032] The pressurizing medium of the pressurization process is compressed air. A constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.1MPa, the heating rate during the constant pressure heating stage is 3℃ / min, the constant pressure is heated to 360℃, the constant pressure insulation time is 0.2h, the cooling rate during the constant pressure cooling stage is 0.5℃ / min, and the temperature after cooling is 150℃; the heat treatment temperature is 170℃, and the heat treatment time is 2h; the cooling rate during the cooling process is 0.2℃ / min, and the temperature after the cooling process is 160℃.

[0033] After the cooling process is completed, the power of the oven is turned off, and the carbon fiber intramedullary nail is obtained after natural cooling to room temperature.

[0034] Example 2

[0035] The difference from Example 1 is that in this example, the central fiber (first layer fiber) is pure magnesium fiber, the single fiber fineness is 200tex, the twist pitch is 125mm, and the cross section is elliptical, the second layer fiber is carbon fiber, the single fiber fineness is 200tex, the twist pitch is 125mm, and the third layer fiber is polyetherketone fiber, the fineness is 300tex, and the twist pitch is 125mm. The second layer fiber and the third layer fiber are twisted in parallel in the Z direction relative to the central fiber to obtain a pure magnesium / carbon fiber / polyetherketone hybrid fiber composite strand.

[0036] The hybrid fiber composite strands were wound in the Z direction at a constant angular rate of 4° / min onto a supporting mandrel in a cylindrical spiral state to obtain a straight-wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 200 mm). During the process, an axial compression load of 6N was applied to the mandrel, and the mandrel and the torsion device were kept coaxial. At the same time, screw holes were formed in the preform by means of a pre-embedded mold. The screw holes were symmetrically arranged and had a hole diameter of 4.0 mm.

[0037] The pressurizing medium of the pressurization process is compressed air. A constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.3MPa, the heating rate during the constant pressure heating stage is 4℃ / min, the temperature is increased to 370℃ at constant pressure, the constant pressure insulation time is 0.4h, the cooling rate during the constant pressure cooling stage is 1.5℃ / min, and the temperature after cooling is 140℃; the heat treatment temperature is 190℃, and the heat treatment time is 4h; the cooling rate during the cooling process is 0.6℃ / min, and the temperature after the cooling process is 150℃.

[0038] Example 3

[0039] The difference from Example 1 is that in this embodiment, the central fiber (first layer fiber) is a zinc-strontium alloy fiber and a carbon fiber twisted in the Z direction, the single fiber fineness is 100tex, and the twist pitch is 100mm. The second layer fiber is an alternating arrangement of magnesium-strontium alloy fiber (single fiber fineness 150tex) and carbon fiber (single fiber fineness 100tex), and the twist pitch is 100mm. The third layer fiber is a polyetherketoneketone fiber with a fineness of 400tex and a twist pitch of 100mm. The second layer fiber and the third layer fiber are twisted in parallel in the Z direction relative to the central fiber to obtain a zinc-strontium alloy fiber + carbon fiber / magnesium-strontium alloy fiber + carbon fiber / polyetherketoneketone fiber hybrid fiber composite strand, wherein the cross sections of the zinc-strontium alloy fiber and the magnesium-strontium alloy fiber are both flat.

[0040] The hybrid fiber composite strands were wound in the Z direction at a constant angular rate of 5° / min onto a supporting mandrel in a cylindrical spiral state to obtain a straight-wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 250 mm). During the process, an axial compression load of 7N was applied to the mandrel, and the mandrel and the torsion device were kept coaxial. At the same time, screw holes were formed in the preform by means of a pre-embedded mold. The screw holes were symmetrically arranged and had a hole diameter of 6.0 mm.

[0041] The pressurizing medium of the pressurization process is compressed air. A constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.5MPa. The heating rate during the constant pressure heating stage is 5℃ / min. The temperature is raised to 380℃ at constant pressure, and the constant pressure insulation time is 0.6h. The cooling rate during the constant pressure cooling stage is 2.5℃ / min, and the temperature after cooling is 130℃. The heat treatment temperature is 210℃, and the heat treatment time is 6h. The cooling rate during the cooling process is 1℃ / min, and the temperature after the cooling process is 140℃.

[0042] Example 4

[0043] The difference from Example 1 is that in this embodiment, the central fiber (first layer fiber) is carbon fiber, the single fiber fineness is 150tex, and the twist pitch is 150mm, the second layer fiber is zinc-lithium-magnesium alloy fiber, the single fiber fineness is 200tex, and the twist pitch is 150mm, and the third layer fiber is polyetheretherketoneketone fiber, the fineness is 200tex, and the twist pitch is 150mm. The second layer fiber and the third layer fiber are twisted in parallel in the Z direction relative to the central fiber to obtain a carbon fiber / zinc-lithium-magnesium alloy fiber / polyetheretherketoneketone fiber hybrid fiber composite strand, wherein the cross section of the zinc-lithium-magnesium alloy fiber is a trapezoid.

[0044] The mixed fiber composite rope strands were wound in the S direction at a constant angular rate of 6° / min onto a supporting mandrel in a cylindrical spiral state to obtain a wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 300 mm). During the process, an axial compression load of 8N was applied to the mandrel, and the mandrel and the torsion device were kept coaxial. At the same time, screw holes were formed in the preform by means of a pre-embedded mold. The screw holes were arranged symmetrically and had a hole diameter of 8.0 mm.

[0045] The pressurizing medium of the pressurization process is compressed air. A constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.6MPa, the heating rate during the constant pressure heating stage is 6℃ / min, the constant pressure is heated to 390℃, the constant pressure insulation time is 0.8h, the cooling rate during the constant pressure cooling stage is 3℃ / min, and the temperature after cooling is 130℃; the heat treatment temperature is 230℃, and the heat treatment time is 8h; the cooling rate during the cooling process is 1.4℃ / min, and the temperature after the cooling process is 130℃.

[0046] Example 5

[0047] The difference from Example 1 is that in this embodiment, the central fiber (first layer fiber) is carbon fiber, the single fiber fineness is 100tex, and the twist pitch is 175mm, the second layer fiber is pure zinc fiber, the single fiber fineness is 150tex, and the twist pitch is 175mm, the third layer fiber is polyetherketoneetherketoneketone fiber and pure magnesium fiber, the fineness is 200tex, and the twist pitch is 175mm, and the fourth layer fiber is polyetheretherketone fiber, the fineness is 200tex, and the twist pitch is 200mm. The second to fourth layers of fibers are twisted in parallel to the central fiber in the Z direction to obtain a carbon fiber / pure zinc fiber / polyetherketoneetherketoneketone fiber+pure magnesium fiber / polyetheretherketone fiber mixed fiber composite strand, wherein the cross sections of the pure zinc fiber and the pure magnesium fiber are both wedge-shaped.

[0048] The hybrid fiber composite rope strands were wound in the Z direction at a constant angular rate of 7° / min onto a supporting mandrel in a cylindrical spiral state to obtain a straight-wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 350 mm). During the process, an axial compression load of 9N was applied to the mandrel, and the mandrel and the torsion device were kept coaxial. At the same time, screw holes were formed in the preform by means of a pre-embedded mold. The screw holes were arranged symmetrically and had a hole diameter of 6.0 mm.

[0049] The pressurizing medium of the pressurization process is nitrogen, and a constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.5MPa, the heating rate in the constant pressure heating stage is 7℃ / min, the constant pressure is heated to 400℃, the constant pressure insulation time is 1h, the cooling rate in the constant pressure cooling stage is 3℃ / min, and the temperature after cooling is 130℃; the heat treatment temperature is 250℃, and the heat treatment time is 10h; the cooling rate in the cooling process is 1.8℃ / min, and the temperature after the cooling process is 120℃.

[0050] Example 6

[0051] The difference from Example 1 is that in this example, the central fiber (first layer fiber) is carbon fiber, the single fiber fineness is 35tex, and the twist pitch is 50mm, the second layer fiber is pure zinc fiber, the single fiber fineness is 35tex, and the twist pitch is 50mm, and the third layer fiber is polyetheretherketone fiber, the fineness is 90tex, and the twist pitch is 200mm. The second layer fiber and the third layer fiber are twisted in parallel in the Z direction relative to the central fiber to obtain a carbon fiber / pure zinc fiber / polyetheretherketone fiber hybrid fiber composite strand, wherein the cross section of the pure zinc fiber is circular.

[0052] The hybrid fiber composite strands were wound in the Z direction at a constant angular rate of 8° / min onto a supporting mandrel in a cylindrical spiral state to obtain a straight-wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 400 mm). During the process, an axial compression load of 10 N was applied to the mandrel, and the mandrel and the torsion device were kept coaxial. At the same time, screw holes were formed in the preform by means of a pre-embedded mold. The screw holes were symmetrically arranged and had a hole diameter of 6.0 mm.

[0053] The pressurizing medium of the pressurization process is nitrogen, and a constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate in the range of 0-0.1MPa / min. The constant pressure is 0.5MPa, the heating rate in the constant pressure heating stage is 8℃ / min, the constant pressure is heated to 410℃, the constant pressure insulation time is 1h, the cooling rate in the constant pressure cooling stage is 3℃ / min, and the temperature after cooling is 130℃; the heat treatment temperature is 170℃, and the heat treatment time is 12h; the cooling rate in the cooling process is 2℃ / min, and the temperature after the cooling process is 120℃.

[0054] Example 7

[0055] The difference from Example 1 is that in this embodiment, the central fiber (first layer fiber) is carbon fiber, the single fiber fineness is 330tex, and the twist pitch is 50mm, the second layer fiber is pure iron fiber, the single fiber fineness is 280tex, and the twist pitch is 50mm, and the third layer fiber is polyetheretherketone fiber, the fineness is 550tex, and the twist pitch is 50mm. The second layer fiber and the third layer fiber are twisted in parallel in the Z direction relative to the central fiber to obtain a carbon fiber / pure zinc fiber / polyetheretherketone fiber hybrid fiber composite strand, wherein the cross section of the pure zinc fiber is circular.

[0056] The hybrid fiber composite rope strands were wound in the Z direction at a constant angular rate of 10° / min onto a supporting mandrel in a cylindrical spiral state to obtain a straight-wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 420 mm). During the process, an axial compression load of 10 N was applied to the mandrel, and the mandrel and the torsion device were kept coaxial. At the same time, screw holes were formed in the preform by means of a pre-embedded mold. The screw holes were symmetrically arranged and had a hole diameter of 6.0 mm.

[0057] The pressurizing medium of the pressurization process is nitrogen, and a constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.5MPa, the heating rate in the constant pressure heating stage is 3℃ / min, the constant pressure is heated to 420℃, the constant pressure insulation time is 1h, the cooling rate in the constant pressure cooling stage is 3℃ / min, and the temperature after cooling is 130℃; the heat treatment temperature is 170℃, and the heat treatment time is 2h; the cooling rate in the cooling process is 2℃ / min, and the temperature after the cooling process is 120℃.

[0058] Example 8

[0059] The difference from Example 1 is that in this embodiment, the central fiber (first layer fiber) is carbon fiber, the single fiber fineness is 100tex, and the twist pitch is 175mm, the second layer fiber is iron-manganese alloy fiber, the single fiber fineness is 150tex, and the twist pitch is 175mm, the third layer fiber is polyether ketone ether ketone ketone fiber and pure magnesium fiber, the fineness is 200tex, and the twist pitch is 175mm, and the fourth layer fiber is polyether ether ketone fiber, carbon fiber and magnesium zinc alloy fiber, the fineness is 200tex, and the twist pitch is 200mm. The second to fourth layers of fibers are twisted in parallel Z direction relative to the central fiber to obtain carbon fiber / pure zinc fiber / polyether ketone ether ketone ketone fiber+pure magnesium fiber / polyether ether ketone fiber+carbon fiber+magnesium zinc alloy fiber mixed fiber composite strands, wherein the cross sections of pure zinc fiber, pure magnesium fiber and magnesium zinc alloy fiber are circular.

[0060] The hybrid fiber composite rope strands were wound in the Z direction at a constant angular rate of 10° / min onto a supporting mandrel in a cylindrical spiral state to obtain a straight-wound carbon fiber preform (with a wall thickness of 2.5 mm and a length of 420 mm). During the process, an axial compression load of 10 N was applied to the mandrel, and the mandrel and the torsion device were kept coaxial. At the same time, screw holes were formed in the preform by means of a pre-embedded mold. The screw holes were symmetrically arranged and had a hole diameter of 6.0 mm.

[0061] The pressurizing medium of the pressurization process is nitrogen, and a constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.5MPa, the heating rate in the constant pressure heating stage is 7℃ / min, the constant pressure is heated to 400℃, the constant pressure insulation time is 1h, the cooling rate in the constant pressure cooling stage is 3℃ / min, and the temperature after cooling is 130℃; the heat treatment temperature is 250℃, and the heat treatment time is 10h; the cooling rate in the cooling process is 1.8℃ / min, and the temperature after the cooling process is 120℃.

[0062] Comparative Example 1

[0063] Titanium alloy intramedullary nails are made by CNC machine tools through turning, milling and other processing procedures:

[0064] Select suitable sharp knives, end mills, cut-off knives and chamfering knives and install them in the corresponding tool positions, place the medical grade titanium alloy (Ti6Al4V) polished rod blank in the Swiss-type lathe, and complete the flat end face cutting action. According to the CNC program, turn the outer circle, mill the arc groove, flatten the position, clamp the back shaft and flatten the other end face, and then drill through holes, bend, process the holes, perform preliminary treatment and post-treatment (rough polishing and fine polishing) with deep hole drilling, and use MICRO-90 solution with a mass concentration of 2% and purified water to semi-finely wash, finely wash and dry the polished parts in turn. Finally, place the workpiece in the electrolyte according to the needs and adjust the parameters such as voltage and time to control the oxidation color to obtain the titanium alloy intramedullary nail.

[0065] Comparative Example 2

[0066] The outer layer fibers are spirally wound around the central fibers to prepare a hybrid fiber composite strand. In this embodiment, the central fiber (first layer fiber) is a carbon fiber with a single fiber fineness of 200 tex and a twist pitch of 75 mm. The second layer fiber is a magnesium-zinc alloy fiber with a single fiber fineness of 100 tex, a twist pitch of 75 mm, and a circular cross section. The third layer fiber is a polyetheretherketone fiber with a fineness of 200 tex and a twist pitch of 75 mm. The second layer fiber and the third layer fiber are twisted in parallel in the Z direction relative to the central fiber to obtain a CF / Mg-Zn / PEEK (carbon fiber / magnesium-zinc alloy / polyetheretherketone) hybrid fiber composite strand.

[0067] Using polyetheretherketone fiber yarn as suture thread, a steel needle is used to repeatedly pierce 6 strands of mixed fiber composite rope and sew them into the outer wall of the core mold in parallel to obtain a carbon fiber preform (wall thickness 3.2mm, length 380mm), in which screw holes are formed in the preform by pre-embedded mold, the screw holes are arranged symmetrically, and the hole diameter is 2.0mm.

[0068] The carbon fiber preform is sequentially hot pressed, cooled and heat treated to obtain an integrally formed carbon fiber intramedullary nail.

[0069] Hot pressing includes sealing the carbon fiber preform with a vacuum bag and sequentially undergoing a preheating process and a pressurizing process in an autoclave, and the pressurizing process sequentially includes three stages: constant pressure heating, constant pressure insulation and constant pressure cooling; cooling includes demoulding after natural cooling to room temperature after the pressurizing process; heat treatment includes placing the demoulded carbon fiber preform in a heated heat treatment equipment for insulation, and then going through a cooling process and a natural cooling process.

[0070] The pressurizing medium of the pressurization process is compressed air. A constant pressure heating program is set for the autoclave. The pressure control during the constant pressure heating and constant pressure insulation process keeps the pressure rise / fall rate within the range of 0-0.1MPa / min. The constant pressure is 0.1MPa, the heating rate during the constant pressure heating stage is 3℃ / min, the constant pressure is heated to 360℃, the constant pressure insulation time is 0.2h, the cooling rate during the constant pressure cooling stage is 0.5℃ / min, and the temperature after cooling is 150℃; the heat treatment temperature is 170℃, and the heat treatment time is 2h; the cooling rate during the cooling process is 0.2℃ / min, and the temperature after the cooling process is 160℃.

[0071] After the cooling process is completed, the power of the oven is turned off, and the carbon fiber intramedullary nail is obtained after natural cooling to room temperature.

[0072] The properties of the carbon fiber intramedullary nails prepared in Examples 1-8 and the intramedullary nails prepared in Comparative Examples 1-2 were tested, and the test results are shown in Table 1.

[0073] The bending and torsion performance test methods are based on YY / T0591-2011 "Metallic Locking Intramedullary Nail for Bone Joint Implants";

[0074] The pore content test method is based on GB / T3365-2008 "Test method for pore content and fiber volume content of carbon fiber reinforced plastics";

[0075] The shear performance test method is based on GB / T30969-2014 "Test method for short beam shear strength of polymer matrix composite materials";

[0076] The fracture toughness test method is based on GB / T4161-2007 "Plane Strain Fracture Toughness K of Metallic Materials" IC Test method》.

[0077] Table 1 Performance test results of intramedullary nails in various embodiments and comparative examples

[0078]

[0079] As shown in Table 1, the carbon fiber intramedullary nail prepared by the carbon fiber intramedullary nail preparation method provided by the present application shows initial performance in bending yield load, bending fatigue strength, fracture toughness, and shear load peak performance that is not inferior to that of the titanium alloy intramedullary nail prepared by the traditional method, and shows a porosity higher than 62% at 48 weeks. It can be seen from the table that the bending fatigue strength and fracture toughness of the carbon fiber intramedullary nail provided by the present application are significantly stronger than those of the titanium alloy intramedullary nail prepared by the traditional method, and although the comparative example 2 without twisting forming uses the same material, the fracture toughness is insufficient.

[0080] As can be seen from Table 1, under the complex stress conditions of the human body, the spiral reinforced fiber layer can evenly bear and resist crack propagation, and improve the fracture toughness of the intramedullary nail body. The straight-wound carbon fiber intramedullary nail has better bending and torsion performance, and can withstand higher shear forces without failure under the same cycle.

[0081] Compared with traditional titanium alloy intramedullary nails, the carbon fiber intramedullary nail prepared according to the embodiment can not only meet the requirements of early strong fixation, but also maintain appropriate mechanical support during service, match the mechanical properties and physiological environment of human bones, promote bone tissue repair while degrading, and have significant clinical effects.

[0082] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A method for preparing a carbon fiber intramedullary nail, characterized in that: The following steps are involved: At least two layers of outer fibers are spirally wound around a central fiber to prepare a hybrid fiber composite rope strand; the hybrid fiber composite rope strand is axially loaded and twisted around a core mold to form a spiral carbon fiber preform, and a mold is embedded in the carbon fiber preform to form a screw hole; the carbon fiber preform is sequentially hot-pressed, cooled and heat-treated to obtain an integrally formed carbon fiber intramedullary nail, wherein the fibers of the hybrid fiber composite rope strand include polyaryletherketone resin fibers, carbon fibers and biodegradable metal fibers.

2. The method for preparing a carbon fiber intramedullary nail according to claim 1, characterized in that: The central fiber of the mixed fiber composite strand is the first layer of fiber, the polyaryletherketone resin fiber is arranged in the third layer or the outer layer, the first layer of fiber and the second layer of fiber are carbon fiber and / or biodegradable metal fiber, and the third layer and the outer layer of fiber are one of carbon fiber, biodegradable metal fiber and polyaryletherketone resin fiber or any combination thereof.

3. The method for preparing a carbon fiber intramedullary nail according to claim 2, characterized in that: The biodegradable metal fiber includes one or more combinations of pure zinc fiber, pure magnesium fiber, pure iron fiber, magnesium-based alloy fiber, zinc-based alloy fiber and iron-based alloy fiber.

4. The method for preparing a carbon fiber intramedullary nail according to claim 2, characterized in that: The fineness of the polyaryletherketone resin fiber is 90-550tex, the fineness of the carbon fiber is 35-330tex, and the fineness of the biodegradable metal fiber is 35-280tex.

5. The method for preparing a carbon fiber intramedullary nail according to claim 2, characterized in that: The twisting distance of the polyaryletherketone resin fiber, the carbon fiber and the biodegradable metal fiber wound around the central fiber is 50-200mm.

6. The method for preparing a carbon fiber intramedullary nail according to claim 3, characterized in that: The hybrid fiber composite rope strands are wound onto a supporting mandrel at a constant angular rate, wherein the constant angular rate is 3° / min-10° / min.

7. The method for preparing a carbon fiber intramedullary nail according to claim 5, characterized in that: The length of the carbon fiber preform is 170-420 mm, the axial compression load of the axial loading twisting is 5-10 N, the hole diameter of the screw hole is 2-8 mm, and the cross section of the metal fiber is circular, elliptical, flat, trapezoidal or wedge-shaped.

8. The method for preparing a carbon fiber intramedullary nail according to claim 1, characterized in that: The hot pressing comprises sealing the carbon fiber preform with a vacuum bag and sequentially undergoing a preheating process and a pressurizing process in an autoclave, wherein the pressurizing process sequentially comprises three stages: constant pressure heating, constant pressure insulation and constant pressure cooling; the cooling comprises demoulding after naturally cooling to room temperature after the pressurizing process; the heat treatment comprises placing the demoulded carbon fiber preform in a heated heat treatment device for insulation, and then undergoing a cooling process and a natural cooling process.

9. The method for preparing a carbon fiber intramedullary nail according to claim 8, characterized in that: The pressurizing medium of the pressurization process is compressed air or nitrogen, the pressure increase / depressurization rate of the constant pressure heating and constant pressure insulation process is 0-0.1MPa / min, the constant pressure is 0.1-0.6MPa, the heating rate of the constant pressure heating stage is 3-8℃ / min, the constant pressure heating is to 360-420℃, the constant pressure insulation time is 0.2-1h, the cooling rate of the constant pressure cooling stage is 0.5-3℃ / min, and the temperature after cooling is 130-150℃; the heat treatment temperature is 170-250℃, and the heat treatment time is 2-12h; the cooling rate of the cooling process is 0.2-2℃ / min, and the temperature after the cooling process is 120-160℃.

10. A carbon fiber intramedullary nail, characterized in that: The carbon fiber intramedullary nail is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Biological reactive phosphate based continuous glass fiber textile composite and application thereof

    CN105818492A

  • Continuous carbon fiber reinforced polyether-ether-ketone composite material bone fixing plate

    CN221205624U

  • Hybrid fiber composite rope core, hybrid fiber composite rope core forming process and rope core manufacturing device

    CN103956210A

  • High-strength degradable intramedullary nail and manufacturing method thereof

    CN112451752A

  • Preparation method of three-dimensional hybrid fiber reinforced thermoplastic composite material

    CN113334803A

Cited By

  • Knee joint prosthesis intramedullary nail and preparation method thereof

    CN120501941A